Application of edge computing to the design and planning of urban sculpture space. (27th July 2022) - Huang, Xiaohua; Shao, Yueyun
The purpose of this study is to realise the construction of urban culture and save the cost of urban sculpture space design. First, edge computing technology is combined with urban sculpture space design and planning. Second, the services, architecture, advantages and characteristics of urban sculpture, as well as the key and difficult points in the construction are briefly discussed, and the hierarchical architecture of urban sculpture space based on edge computing is put forward. Then, cloud and edge computing are combined to analyse the specific functions of urban sculpture. On this basis, the architecture platform of the security monitoring system of urban sculpture is constructed. The energy consumption of the optimal path planning algorithm based on reinforcement learning is proposed and compared with that of the previous algorithms. Finally, the actual energy consumption required is predicted and evaluated, and a specific monitoring system is established.